Modern topics in the phototrophic prokaryotes : environmental and applied aspects - Hallenbeck, Patrick C. (Springer, 2017)
This book offers authoritative contributions by world experts actively working on different aspects of phototrophic prokaryotes. Providing up-to-date information in this rapidly advancing field, it covers the range of topics that are currently the focus of research with this group of organisms. As essentially single-celled organisms, phototrophic prokaryotes process many environmental signals and use this information to optimize their metabolism, growth rate, DNA replication and cell division. Phototrophic prokaryotes are collectively of great interest for a number of different fundamental and applied perspectives and have long served as models for understanding such basic fundamental biological processes as photosynthesis and respiration. On an ecological/environmental level they are extremely important, being the most abundant photosynthetic organisms on earth and responsible for the majority of the primary productivity in the oceans. They also hold great promise as biotechnological catalysts, being able to couple solar energy conversion through photosynthesis and carbon fixation to the production of biofuels, commodity chemicals and neutraceuticals. The book is recommended to advanced students and scientists dealing with life sciences, especially in genetics, microbiology and molecular biology.- Resumé vydavatel